Interactive Highlighting for Just-In-Time Formative Assessment During Whole-Class Instruction: Effects on Vocabulary Learning and Reading Comprehension - Lopez-Villarroel, M; Figueroa-Gonzalez, V; Ponce-Arias, H (Routledge, 2018)
This article examines the effectiveness of a software that supports formative assessment in real-time of learners vocabulary knowledge through an interactive highlighting method. Students in a classroom are given a passage on their computer screen and asked to highlight the words they do not understand. This information is summarized on the instructors screen by highlighting in red the words most highlighted, in orange the second most highlighted, and in yellow the third most highlighted, with a superscript showing the number of students who selected each word. The instructor projects this summary on a screen for the whole class and use it to guide activities on how to comprehend the passage. In Experiment 1, college students who learned with interactive highlighting in a single-session study scored higher on a vocabulary test (d = 1.14) but not on a comprehension test as compared to a control group that studied the same passage without interactive highlighting. In Experiment 2, high school students who learned with interactive highlighting across a 10-week program scored higher on a standardized reading comprehension test as compared to a control group that studied without interactive highlighting (d = 1.60 in school 1, d = 1.17 in school 2). © 2017 Informa UK Limited, trading as Taylor & Francis Group.